Digital Transformation Project: Digitalization of Budgeting Process at XYZ - Shafira Amanda Umar; Gatot Yudoko (Department of Management, Faculty of Economics and Business, Brawijaya University, 2022)
Indonesia is one of Southeast Asia's country with the fastest-growing digital economies. State-owned enterprises (SOEs) or Badan Usaha Milik Negara (BUMN) can play a significant role in supporting Indonesia in its digital transformation. One of the SOEs that has used technologies to aid in the digital transformation is XYZ company. Currently, there is an ongoing project of budgeting process digitalization using Anaplan's integrated cloud-based platform which consists of three phases. This research aims to identify root causes of issues occurring in Phase 1, generate solutions to address the root causes, and prevent the same issues to happen in Phase 2. Current issues are related to system inflexibility, XYZ human capital, system bugs, and XYZ reporting complexity, which are rooted from five root causes. It has been discussed that only four out of five root causes can be solved since they are still within XYZ’s reach. This research generates six proposed solutions utilizing PMBOK Project Resource Management Knowledge Area and Organizational Process Assets (OPA). There are three prioritized solutions that need to be implemented soon before starting Phase 2, which are lessons learned discussion and documentation, knowledge transfer, and budgeting guideline formulation.